Cyfrowe narzędzia w dydaktyce akademickiej. Badania diachroniczne polskiej fleksji z użyciem systemu Chronofleks - Kinga Wąsińska (Forum Lingwistyczne, 2020)
This paper describes the possibilities of the diachronic description of Polish inflection by the Chronofleks system and using it in academic didactics of historical linguistics classes. In new didactic seems necessary to use solutions based on new technologies that use students’ digital skills. Therefore, the observations carried out were to check the extent to which Chronofleks is helpful both in verifying the information available in academic textbooks and in the independent acquisition of knowledge by students. Three grammar issues were selected for research: Kopczyński’s rules, distribution of historic singular endings of male nouns, and ending frequency of the first person plural of verbs. The tests showed that a student can successfully learn the morphology of old Polish using the Chronofleks tool. In addition, Chronofleks allows you to implement a self-study teaching model.